2013
DOI: 10.3390/w6010068
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Assessment of Groundwater Quality Monitoring Wells Using Indicator Kriging and Risk Mapping, Amol-Babol Plain, Iran

Abstract: Abstract:The main aim of monitoring wells is to assess the conditions of groundwater quality in the aquifer system. An inappropriate distribution of sampling wells could produce insufficient or redundant data concerning groundwater quality. An optimal selection of representative monitoring well locations can be obtained by considering the natural and anthropogenic potential of pollution sources; the hydrogeological setting; and assessment of any existing data regarding monitoring networks. The main objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Due to the high cost of sampling in ocean, an optimization method is needed to improve the efficiency of the outdated monitoring network with a limited number of sites. Because the movement and transfer mechanisms within marine environments are not entirely clear, statistical methods are often used to optimize marine environmental monitoring networks (Lin and Rouhani 2001, Shen and Wu 2013, Sheikhy Narany et al 2013. In space-time sampling, Gruijter et al (2006) distinguished several basic design types, including static, independent synchronous, static-synchronous, supplemented panel, and serially alternating.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high cost of sampling in ocean, an optimization method is needed to improve the efficiency of the outdated monitoring network with a limited number of sites. Because the movement and transfer mechanisms within marine environments are not entirely clear, statistical methods are often used to optimize marine environmental monitoring networks (Lin and Rouhani 2001, Shen and Wu 2013, Sheikhy Narany et al 2013. In space-time sampling, Gruijter et al (2006) distinguished several basic design types, including static, independent synchronous, static-synchronous, supplemented panel, and serially alternating.…”
Section: Introductionmentioning
confidence: 99%
“…For the analyzed area, empirical (experimental) variogram was drawn, which presents dependencies between the variance and distance between the sampling points [28]. The obtained experimental variogram is characterized by quite a regular shape, which probably results from the number of the analyzed measuring points.…”
Section: Water Network Infrastructure Variantsmentioning
confidence: 99%
“…Dutta et al (1998) employed the vulnerability index (calculated with the DRASTIC method proposed by Aller et al 1987), industry and stream network coverage, and data of some sampled water quality parameters to suggest different monitoring alternatives, but considered only the parameter with the largest variance in the optimization process. Narany et al (2013) presented a methodology that combines, through a geographic information system, a risk map (calculated from the vulnerability index and land use) and a map of the groundwater nitrate thresholds exceedance probability (obtained with indicator kriging); the highest combined index represents areas in which there is a very strong probability of elevated nitrate concentrations and therefore a higher risk of contamination. The monitoring network was proposed by a visual procedure; the authors concluded that a monitoring network design should consider both the risks and the current state of contamination.…”
Section: Introductionmentioning
confidence: 99%